PENGARUH NOVEL KIMIA DALAM KEGIATAN PEMBELAJARAN TERHADAP PEMAHAMAN KONSEP DAN MOTIVASI BELAJAR - Zulfah, Zulfah (Jurnal Penelitian dan Pembelajaran IPA, 2016)
AbstractThis research aimed to determine the effect of using chemical novel in learning activities to the understanding of concept and learning motivation in class X SMA Muhammadiyah 3 Yogyakarta of the school year 2012-2013. The research design is non equivalent control group design. Data is collected using pretest and post-test booklet and sheet scale learning motivation to the using chemical novel. The results of the data analysis in this research is on the motivation of learners average experimental and control classes, respectively 72.79 and 69.43. The results showed that the average experimental class on learning motivation is greater than the average grade control. The average is categorized according to both Sukardjo which is between 67.998 and 83.994. In aspect of understanding the concept, for posttest data is normally distributed with sig-class experimental and control respectively were 0.08 and 0.35. In homogeneity test data is homogeneous with sig 0.322. The average value of each class posttests were 70.44 and 65.33. Furthermore, using one way ANOVA that shows the value of Farithmetic>Ftable is 4.787> 3.995. This means chemical novel as learning resource on hydrocarbons gives a positive influence on chemistry learning activities.Keywords: Chemical novel, learning motivation, understanding of concept